Rates of Epidural Blood Patch following Lumbar Puncture Comparing Atraumatic versus Bevel-Tip Needles Stratified for Body Mass Index - Philip, J.T.; Flores, M.A.; Beegle, R.D.; Dodson, S.C.; Messina, S.A.; Murray, J.V. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Postdural puncture headache, a known complication of lumbar puncture, typically resolves with conservative management. Symptoms persist in a minority of patients, necessitating an epidural blood patch. One method of decreasing rates of postdural puncture headache is using atraumatic, pencil-point needles rather than bevel-tip needles. To the best of our knowledge, this is the first study comparing epidural blood patch rates between pencil- and bevel-tip needles with a subgroup analysis based on body mass index.MATERIALS AND METHODS: This single-institution retrospective study identified 4435 patients with a recorded body mass index who underwent a lumbar puncture with a 22-ga pencil-tip Whitacre needle, a 20-ga bevel-tip Quincke needle, or a 22-ga Quincke needle. The groups were stratified by body mass index. We compared epidural blood patch rates between 22-ga pencil-tip Whitacre needles versus 22-ga Quincke needles and 22-ga Quincke needles versus 20-ga bevel-tip Quincke needles using the Fischer exact test and χ2 test.RESULTS: Postdural puncture headache necessitating an epidural blood patch was statistically more likely using a 22-ga Quincke needle in all patients (P < .001) and overweight (P = .03) and obese (P < .001) populations compared with using a 22-ga pencil-tip Whitacre needle. In the normal body mass index population, there was no statistically significant difference in epidural blood patch rates when using a 22-ga pencil-tip Whitacre needle compared with a 22-ga Quincke needle (P = .12). There was no significant difference in epidural blood patch rates when comparing a 22-ga Quincke needle versus a 20-ga bevel-tip Quincke needle in healthy (P = .70), overweight (P = .69), or obese populations (P = .44).CONCLUSIONS: Using a 22-ga pencil-tip Whitacre needle resulted in lower epidural blood patch rates compared with a 22-ga Quincke needle in all patients. Subgroup analysis demonstrated a statistically significant difference in epidural blood patch rates in overweight and obese populations, but not in patients with a normal body mass index.BMIbody mass indexEBPepidural blood patchLPlumbar puncturePDPHpostdural puncture headache20Q20-ga bevel-tip Quincke needle22Q22-ga bevel-tip Quincke needle22W22-ga pencil-tip Whitacre needle